Italian industrial districts between offshoring and back-reshoring strategies - Ferrucci, Luca; Picciotti, Antonio (Piccola Impresa / Small Business, 2017)
Italian industrial districts have always showed a high international openness which can be related first to their high propensity to export and, later, to their off-shoring activities in foreign countries. However, in the current competitive scenario, some enterprises are reconsidering their internationalization strategies, evaluating competitive conditions present in their district context and pursuing back-reshoring strategies. This work is placed in this field of studies and aims to provide a theoretical contribution in order to interpret the internationalization strategies of district enterprises, highlighting the antecedents of the back-reshoring and the emergence of a structural variety of strategic behavior in the international markets